A study on the efficiency of supply chain management of oil and gas company / Siti Norkamaria Yahya - Yahya, Siti Norkamaria (2010)
Recent years, Supply chain management (SCM) becomes more important in business competition. It is a major component of strategy to enhance organizational productivity and profitability. Transparency in supply chain management operation and collaboration is very important for success and help business in its journey towards global championship. Nowadays, the organizational performance measurement pertaining SCM has been received attention from researcher and practitioners. In this study, the researcher will measure the efficiency of supply chain based on the four phase activities processes: (i) plan; (ii) source; (iii) make; and (iv)deliver. Each of these phases has their measures to discuss (Stewart, 1995; Gunasekaran et al, 2001; Gunasekaran & Ngai, 2004). The supply chain management measurement aims for improved customer satisfaction and hence for overall competitiveness in Oil and Gas Company for a global market.